The analysis of development in Lithuanian economy and business - Jakutis, Algirdas; Kazlovas, Valentinas (Business: Theory and Practice, 2006)
In this article development tendencies of Lithuanian economy and business are analyzed. The paper examines the most important causes of gross domestic product changes since restoration of Lithuania’s independence. Processes of privatization, their influence on business are analyzed. A brief analysis of development trends of small and medium-sized business in presented. Business development process is analyzed, technological indicators suggested. The article considers business financing issues, characterizes peculiarities of business formation in Lithuania.Article in Lithuanian.Lietuvos ūkio ir verslo raidos analizėSantrauka. Siame straipsnyje aprašomas Lietuvos ūkio ir verslo raidos tendencijos nuo nepriklausomybės atgavimo pradžios. Paaiškinamos svarbiausios bendrojo vidaus produkto kitimo priežastys, aptariami privatizavimo procesai, jų poveikis verslui. Apžvelgiamos smulkiojo ir vidutinio verslo raidos tendencijos. Analizuojami verslo plėtros klausimai, technologiniai rodikliai. Aptariama verslo finansavimo svarba bei nurodomi Lietuvos verslo pradžios specifiniai bruožai.Reikšminiai žodžiai: BVP, privatizacija, verslo raidos tendencijos, technologiniai rodikliai, verslo finansavimas.